Undergraduate Students’Awareness, Usage and Attitude towards Digital Library in Kathmandu - Padam Bahadur Lama; Jung Bahadur Hamal (Interdisciplinary Journal of Management and Social Sciences, 2022)
The study aims at assessing the perception of undergraduate students towards awareness, usage and attitude to digital library in Kathmandu. The study employed a cross-sectional descriptive research design for the primary data collected through structured questionnaire from the sample of respondents with 218 useable responses, 39 percent response rate, from the pool of students of special programs of management faculty of Tribhuvan University, BBA and BBM. The findings of the survey depicted that students were aware of the digital library, found the search function to be useful, and were pleased display output. Students were interested in learning on new advancement, found speedy download, accessible, improved research skills, high-quality research and prompt information in digital library. However, fewer respondents used the 20 mentioned digital library portals than expected and found difficulty due to limited access of digital library that impacted on material collection, compelled to visit other libraries physically, enhanced fear of finishing work and affected research work.